Draft Annual Plan 2000-2001 Statements Union Territory of Pondicherry - Planning Commission (Planning Commission, 2000)
Proposed Outlays, Physical Targets And Achievements, Proposal For Spillover And Ongoing Programmes/Projects As In Annexure-I, Proposals For Maximising Benefits Of Completed Programmes/Projects As On 31.3.2000, Proposal For Programmes/Projects - New Schemes, Summary Statements - Proposals For Programmes/Projects, Statement Regarding Externally Aided Projects Outlays - By Heads Of Development - For District Plans, Centrally Sponsored Scheme, Basic Minimum Services - Outlay & Expenditure, Basic Minimum Services - Physical Targets & Achievements Tribal Sub-Plan - Financial Outlay And Physical Targets, Special Component Plan - Financial Outlays, Special Component Plan - Physical Targets, Voluntary Sectors - Financial Outlay / Expenditure, Women Sub-Plan - Financial Outlays, Women Sub-Plan - Physical Targets, Evaluation Studies
Government of Pondicherry Planning and Research Department
Government of Pondicherry Planning and Research Department
Keywords: Annual Plan; 2000-01; Statements; Bharat Nirman Programmes; Tribal Sub Plan; Financial Outlays; Transport; Centrally Sponsored Schemes; Externally Aided Projects